Faith in Transformation: Eskridge Covenanter Church and the Reformed Presbyterian Church of North America, Eskridge, Kansas, 1884-1964 - Lin, Bo (Kansas State University, The Chapman Center for Rural Studies, 2017)
This is an exploration of the Covenanter Church in Eskridge, Wilmington Township, Wabaunsee County. The Eskridge Covenanter Church belongs to the Reformed Presbyterian Church, which was from the Reformed Presbyterian Church of Scotland. This study of the Covenanter Church relies on church records, interviews, historic atlases, old photographs, and Old World history.
Bo Lin, “Faith in Transformation: Eskridge Covenanter Church and the Reformed Presbyterian Church of North America, Eskridge, Kansas, 1884-1964,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/242.
Keywords: Atchison Topeka & Santa Fe; Eskridge Covenanter Church; Presbyterian Church; Protestant Reformation; Wabaunsee County; Wilimington Township